IONOLUMINESCENCE OF LEUCOPHANITE - Friis H.; Finch A.A.; Townsend P.D.; Hole D.E.; El Mkami H. (My University, 2007)
The luminescence of three natural samples of leucophanite (ideally, NaCaBeSi2O6F) has been investigated with ion-beam excitation and by electron spin resonance (ESR). A blue luminescence, ascribed to a defect associated with SiO4, or BeO4, tetrahedra, and an orange luminescence, ascribed to an Mn2+ center, dominates the emission. Further luminescence centers in the investigated wavelength range (200-1100 nm) include those related to Gd3+, Dy3+., Tb3+, Sm3+, Eu3+, Tm3+, and Nd3+. In spite of a sheet-like structure, leucophanite is relatively resilient to the ion implantation and β-irradiation, compared with other minerals, but loss of luminescence intensity as a function of implantation show that some permanent defects are formed. No centers change their emission energy as a function of temperature in the investigated interval (40-300 K), but due to crystal-field interaction, a broadening of the Mn2+ emission band is observed with increasing temperature, and with low activator concentration. The variation in activator concentration is clearly seen from a pronounced concentration quenching. ESR data (9.7 and 188 GHz) show that Mn is only present in one crystallographic site and that the REE-richest sample has an additional signal with g ~ 2.003. No new defects could be seen with ESR in a β-irradiated sample.
Keywords: ESR; IONOLUMINESCENCE; LANTHANIDE; LEUCOPHANITE; MN2+; REE